Evidence for an imbalance between tau O-GlcNAcylation and phosphorylation in the hippocampus of a mouse model of Alzheimer's disease. (March 2016) - Gatta, Eleonora; Lefebvre, Tony; Gaetani, Silvana; Dos Santos, Marc; Marrocco, Jordan; Mir, Anne-Marie; Cassano, Tommaso; Maccari, Stefania; Nicoletti, Ferdinando; Mairesse, Jérôme
Graphical abstract: Abstract: Intracellular accumulation of hyperphosphorylated tau protein is linked to neuronal degeneration in Alzheimer's disease (AD). Mounting evidence suggests that tau phosphorylation and O - N -acetylglucosamine glycosylation ( O -GlcNAcylation) are mutually exclusive post-translational modifications. O -GlcNAcylation depends on 3–5% of intracellular glucose that enters the hexosamine biosynthetic pathway. To our knowledge, the existence of an imbalance between tau phosphorylation and O -GlcNAcylation has not been reported in animal models of AD, as yet. Here, we used triple transgenic (3xTg-AD) mice at 12 months, an age at which hyperphosphorylated tau is already detected and associated with cognitive decline. In these mice, we showed that tau was hyperphosphorylated on both Ser396 and Thr205 in the hippocampus, and to a lower extent and exclusively on Thr205 in the frontal cortex. Tau O -GlcNAcylation, assessed in tau immunoprecipitates, was substantially reduced in the hippocampus of 3xTg-AD mice, with no changes in the frontal cortex or in the cerebellum. No changes in the expression of the three major enzymes involved in O -GlcNAcylation, i.e., glutamine fructose-6-phosphate amidotransferase, O -linked β- N -acetylglucosamine transferase, and O -GlcNAc hydrolase were found in the hippocampus of 3xTg-AD mice. These data demonstrate that an imbalance between tau phosphorylation and O -GlcNAcylation exists in AD mice, and strengthens the hypothesis that O -GlcNAcylation might be targeted by disease modifying drugs in AD.